2021
DOI: 10.3390/ijms222011148
|View full text |Cite
|
Sign up to set email alerts
|

The Role of MAPK3/1 and AKT in the Acquisition of High Meiotic and Developmental Competence of Porcine Oocytes Cultured In Vitro in FLI Medium

Abstract: The developmental potential of porcine oocytes cultured in vitro was remarkably enhanced in a medium containing FGF2, LIF and IGF1 (FLI) when compared to a medium supplemented with gonadotropins and EGF (control). We analyzed the molecular background of the enhanced oocyte quality by comparing the time course of MAPK3/1 and AKT activation, and the expression of genes controlled by these kinases in cumulus-oocyte complexes (COCs) cultured in FLI and the control medium. The pattern of MAPK3/1 activation in COCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…It is common to have supplements in the medium that act additively to improve in vitro embryo production, with publications showing an increase in the blastulation rates after treatment with individual cytokines, separately as well as in combination (Valleh et al, 2017;Yuan, et al, 2017;Stoecklein et al, 2021) showed that the combination of FLI with gonadotropins enhanced oocyte development and improved cumulus cell expansion. Procházka et al (2021) demonstrated a similar activation pattern of MAPK3/1 between medium supplemented with or without FLI, showing only an increase in MAPK3/1 phosphorylation during the first hour of culture in the FLI medium. This suggests that COCs cultured with FLI experience enhanced MAPK3/1 stimulation that resulted in the development of highly competent oocytes.…”
Section: Discussionmentioning
confidence: 69%
“…It is common to have supplements in the medium that act additively to improve in vitro embryo production, with publications showing an increase in the blastulation rates after treatment with individual cytokines, separately as well as in combination (Valleh et al, 2017;Yuan, et al, 2017;Stoecklein et al, 2021) showed that the combination of FLI with gonadotropins enhanced oocyte development and improved cumulus cell expansion. Procházka et al (2021) demonstrated a similar activation pattern of MAPK3/1 between medium supplemented with or without FLI, showing only an increase in MAPK3/1 phosphorylation during the first hour of culture in the FLI medium. This suggests that COCs cultured with FLI experience enhanced MAPK3/1 stimulation that resulted in the development of highly competent oocytes.…”
Section: Discussionmentioning
confidence: 69%
“…Maturation rates of porcine oocytes in DMEM correlate with multiple outcomes achieved from different labs as Yuan, Krisher and Procházka et al where the maturation success rate of up to 89.70% was attained in TCM-199. Maturation in FLI media results in a significantly higher level of MII oocytes 18 , 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that cAMP modulators enhance the developmental competence of porcine oocytes after IVF and SCNT. The use of cAMP modulators during IVM results in the proper cytoplasmic maturation of oocytes to support the subsequent embryonic development [78][79][80] . Another study reported that cAMP modulators, including cilostamide and forskolin, effectively cause meiotic arrest in the oocytes following pre-IVM for 24 h 32 .…”
Section: Discussionmentioning
confidence: 99%